Perovskite solar cell and preparation method thereof

The perovskite layer is modified by hydroxybenzoic acid crosslinking agent, which solves the brittleness of flexible perovskite solar cells under mechanical stress, achieves efficient photoelectric conversion and excellent mechanical stability, improves conductivity and has self-healing ability.

CN120475882AActive Publication Date: 2025-08-12TAIYUAN UNIVERSITY OF TECHNOLOGY
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202510648951.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-05-20
Publication Date
2025-08-12
Estimated Expiration
2045-05-20

AI Technical Summary

Technical Problem

Flexible perovskite solar cells are prone to fracture under mechanical stress, have poor mechanical stability, and their conductivity decreases when improving mechanical stability, affecting the photoelectric conversion efficiency.

Method used

The perovskite layer is modified by hydroxybenzoic acid crosslinking agent, and the network structure is formed through the action of hydroxyl, carboxyl and benzene rings, which reduces Young's modulus, promotes the growth of perovskite crystals, passivates grain boundary defects, and improves conductivity.

Benefits of technology

At the same time, the mechanical stability and photoelectric conversion efficiency of perovskite solar cells are improved, the conductivity is improved, and the self-healing ability is provided.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120475882A_ABST
    Figure CN120475882A_ABST
Patent Text Reader

Abstract

The invention discloses a perovskite solar cell and a preparation method thereof, the preparation method comprises a step of preparing a perovskite light absorption layer, and the step of preparing the perovskite light absorption layer comprises the following steps: spin-coating a dissolved lead iodide precursor solution on a substrate with a carrier transport layer deposited on the surface, and carrying out heating treatment to prepare a lead iodide film; spin-coating the lead iodide thin film with an organic halogenated ammonium salt solution containing a hydroxybenzoic acid cross-linking agent, and carrying out heating treatment to obtain a perovskite thin film; wherein the hydroxybenzoic acid cross-linking agent at least comprises hydroxyl, carboxyl and a benzene ring. The performance of the perovskite light absorption layer prepared by the method is obviously improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of solar cells, and in particular to a perovskite solar cell and a preparation method thereof. Background Art

[0002] Flexible perovskite solar cells have attracted widespread attention due to their advantages such as flexibility, light weight, high power-to-weight ratio, low cost, and low-temperature processability. In recent years, flexible perovskite solar cells have developed rapidly, and their efficiency and stability have been improved to a certain extent, but there is still a certain gap from industrialization. In some currently disclosed flexible perovskite solar cell solutions, the Young's modulus of the perovskite film is still relatively high, which makes it brittle under mechanical stress, causing the perovskite film to easily break during the bending and stretching process of the device, and the mechanical stability is poor. In addition, in some solutions, while improving mechanical stability, it is impossible to take into account conductivity at the same time, which reduces the conductivity of the device's photoelectric absorption layer, affects the transmission of carriers, and restricts the photoelectric conversion efficiency of the device. Summary of the Invention

[0003] The present invention provides a perovskite solar cell and a method for preparing the same. By modifying the perovskite layer with a hydroxybenzoic acid crosslinker, the aforementioned shortcomings of the prior art are addressed. The modified perovskite solar cell exhibits excellent photoelectric conversion efficiency and outstanding mechanical stability. Furthermore, the preparation method is simple, facilitating industrial application.

[0004] An embodiment of the present invention provides a method for preparing a perovskite solar cell, comprising the steps of preparing a perovskite light absorbing layer on a substrate, wherein the perovskite light absorbing layer is modified with a hydroxybenzoic acid crosslinking agent; the steps of preparing the perovskite light absorbing layer include:

[0005] The lead iodide thin film is prepared by spin coating the dissolved lead iodide precursor solution on a substrate with a carrier transport layer deposited on the surface, and then heating the substrate.

[0006] Spin-coating an organic ammonium halide salt solution containing a hydroxybenzoic acid cross-linking agent on the lead iodide film, and heating the solution to obtain a perovskite light absorption layer on the carrier transport layer;

[0007] Wherein, the hydroxybenzoic acid cross-linking agent contains at least a hydroxyl group, a carboxyl group and a benzene ring.

[0008] In some embodiments, the hydroxybenzoic acid crosslinking agent is one of p-hydroxybenzoic acid, o-hydroxybenzoic acid, m-hydroxybenzoic acid, 2-hydroxyterephthalic acid, and 2-hydroxy-1,3,5-benzenetricarboxylic acid.

[0009] In some embodiments, the lead iodide thin film is prepared by spin-coating the dissolved lead iodide precursor solution on a substrate having a carrier transport layer deposited on the surface, and then heating the substrate. Specifically, the process includes:

[0010] Dissolving lead iodide in a mixed solvent of N,N-dimethylformamide (DMF) and dimethyl sulfoxide (DMSO), and then performing a spin coating process and an annealing process to prepare the lead iodide film;

[0011] An organic ammonium halide salt solution containing a hydroxybenzoic acid crosslinking agent is spin-coated on the lead iodide film, and subjected to heat treatment to obtain a perovskite light absorption layer located on the carrier transport layer, specifically comprising:

[0012] MA containing the hydroxybenzoic acid cross-linking agent x FA 1-x Br y I z Cl 1-y-z An organic ammonium halide salt solution is spin-coated on the lead iodide film and subjected to heat treatment to obtain a perovskite light absorption layer in contact with the carrier transport layer; wherein x is a number less than 1, and y and z are numbers less than 1.

[0013] In some embodiments, the spin coating and annealing conditions for preparing the lead iodide film include: a spin coating rate ranging from 1700 to 1800 r / min, a spin coating time ranging from 25 to 35 s; an annealing temperature ranging from 70 to 100° C. on a heating stage, and an annealing time ranging from 1 to 2 min;

[0014] The spin coating and annealing conditions for preparing the perovskite light absorbing layer include: a spin coating rate ranging from 1500 to 1700 r / min, a spin coating time ranging from 20 to 60 s; an annealing time ranging from 10 to 60 min on a heating stage, and an annealing temperature ranging from 80 to 120° C.

[0015] In some embodiments, the volume ratio of the mixed solvent of N, N-dimethylformamide DMF and dimethyl sulfoxide DMSO is 19:1; MA containing the hydroxybenzoic acid cross-linking agent x FA 1-x Br y I z Cl 1-y-z The concentration of the hydroxybenzoic acid cross-linking agent in the organic ammonium halide solution is 1 to 2 mmol / mL;

[0016] The organic halide ammonium salt mixed solution is a mixture of formammonium iodide FAI, methylammonium bromide MABr, and methylammonium chloride MACl, which is then dissolved in an isopropanol solution to form MACl. x FA 1-x Br y I zCl 1-y-z solution.

[0017] An embodiment of the present invention provides a perovskite solar cell, comprising a substrate, a first carrier transport layer located on the substrate, and a perovskite light absorption layer located on and in contact with the first carrier transport layer, wherein the perovskite light absorption layer is modified with a hydroxybenzoic acid crosslinker; the hydroxybenzoic acid crosslinker contains at least a hydroxyl group, a carboxyl group, and a benzene ring.

[0018] In some embodiments, the Young's modulus of the perovskite light absorbing layer ranges from 24 GPa to 26 GPa.

[0019] In some embodiments, the conductivity of the perovskite light absorbing layer is in the range of 8×10 -5 S / cm~10×10 -5 S / cm.

[0020] In some embodiments, the method further includes a first electrode located on the substrate; the first electrode is located between the substrate and the first carrier transport layer;

[0021] It also includes a second carrier transport layer and a second electrode sequentially located on the perovskite light absorbing layer.

[0022] In some embodiments, the first carrier transport layer is an electron transport layer, the second carrier transport layer is a hole transport layer, the first electrode is a cathode, and the second electrode is an anode; or

[0023] The first carrier transport layer is a hole transport layer, the second carrier transport layer is an electron transport layer, the first electrode is an anode, and the second electrode is a cathode.

[0024] Some embodiments of the present invention further provide a perovskite solar cell, which is manufactured using the preparation method of any of the aforementioned embodiments.

[0025] Compared with the prior art, the present invention has the following beneficial effects:

[0026] The light-absorbing layer of a perovskite solar cell provided by the present invention is obtained by spin-coating a mixed solution of an organic ammonium halide salt doped with a hydroxybenzoic acid crosslinker onto a lead iodide film formed from a lead iodide solution, followed by heat treatment. This method is simple, and the resulting perovskite solar cell can at least improve the conductivity of the perovskite light-absorbing layer and reduce Young's modulus, thereby achieving excellent mechanical stability while improving photoelectric conversion efficiency. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings required for use in the embodiments or the description of the prior art. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.

[0028] Figure 1 A diagram showing the structure of a solar cell according to the present invention;

[0029] Figure 2 (a) is a scanning electron microscope image of the perovskite light absorption layer of the control group, and the average particle size of the perovskite grains is 584nm;

[0030] Figure 2 (b) is a scanning electron microscope morphology of the perovskite light absorption layer modified with a p-hydroxybenzoic acid crosslinker according to an embodiment of the present invention, and the average particle size of the perovskite grains is 937 nm;

[0031] Figure 3 (a) is the atomic force microscope morphology of the perovskite light absorption layer of the control group. The average roughness of the perovskite film surface is 24.2nm;

[0032] Figure 3 (b) is an atomic force microscope morphology image of the perovskite light absorption layer modified with a p-hydroxybenzoic acid crosslinker according to an embodiment of the present invention. The average roughness of the perovskite film surface is 11.5 nm.

[0033] Figure 4 (a) is the conductivity diagram of the perovskite light absorption layer of the control group, and the calculated conductivity is 7.1×10 -5 S / cm;

[0034] Figure 4 (b) is the conductivity diagram of the perovskite light absorption layer modified by the p-hydroxybenzoic acid crosslinker according to the embodiment of the present invention. The calculated conductivity is 9.3×10 -5 S / cm;

[0035] Figure 5 (a) shows the current density-voltage curve of the rigid perovskite solar cell in the control group measured under AM1.5G sunlight, and the photoelectric conversion efficiency of the cell is 22.32%;

[0036] Figure 5 (b) is the current density-voltage curve of the rigid perovskite solar cell modified with a p-hydroxybenzoic acid crosslinker according to an embodiment of the present invention, and the photoelectric conversion efficiency of the cell is 24.76%;

[0037] Figure 6(a) is the nanoindentation test image of the perovskite light absorption layer of the control group. The elastic modulus of the perovskite light layer is calculated to be 40.19 GPa;

[0038] Figure 6 (b) is a nanoindentation test image of the perovskite light absorption layer modified with a p-hydroxybenzoic acid crosslinker according to an embodiment of the present invention. The elastic modulus of the perovskite light absorption layer is calculated to be 25.05 GPa.

[0039] Figure 7 (a) is the current density-voltage curve of the control group flexible perovskite solar cell measured under AM1.5G sunlight, and the photoelectric conversion efficiency of the cell is 20.69%;

[0040] Figure 7 (b) is the current density-voltage curve of the flexible perovskite solar cell modified with a p-hydroxybenzoic acid crosslinker according to an embodiment of the present invention, and the photoelectric conversion efficiency of the cell is 22.73%.

[0041] Figure 8 (a) is a normalized statistical graph of the efficiency of the control group flexible perovskite solar cell after being bent 10,000 times at a bending radius of 5 mm. It is found that the efficiency of the battery is 0 after maintaining 4,000 bending cycles;

[0042] Figure 8 (b) is a normalized statistical graph of the efficiency of a flexible perovskite solar cell modified with a p-hydroxybenzoic acid crosslinker according to an embodiment of the present invention, which was bent 10,000 times at a bending radius of 5 mm. It was found that the battery can maintain 91% of its original efficiency after 10,000 bending cycles.

[0043] Figure 9 (a) is a normalized statistical graph of the efficiency of flexible perovskite solar cells in the control group after self-healing treatment, which can recover to 45% of the original efficiency after self-healing;

[0044] Figure 9 (b) Normalized statistical graph of the efficiency of the flexible perovskite solar cell modified with a crosslinker after self-healing treatment in an embodiment of the present invention, which can recover to 89% of the original efficiency after self-healing. DETAILED DESCRIPTION

[0045] The following will clearly and completely describe the technical solutions in the embodiments of the present invention in conjunction with the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative efforts are within the scope of protection of the present invention.

[0046] Some researchers have applied crosslinkers to perovskite solar cells, hoping that the crosslinkers and perovskites will combine into chain or network structures, forming a flexible crosslinked elastomeric scaffold and improving the flexibility and toughness of the perovskite film. For example, perovskite solar cells modified with carboxylate crosslinkers can effectively release mechanical stress at the perovskite grain boundaries. However, when faced with complex stress environments, the perovskite film will still break and cannot be repaired, resulting in permanent degradation of device performance. For example, crosslinked elastomeric polymers such as polyurethane can release residual stress in flexible films through in situ crosslinking, but the presence of elastomeric polymers at the perovskite grain boundaries will cause an electrical insulation effect, thereby reducing the conductivity of the perovskite film. It is impossible to ensure both mechanical stability and conductivity.

[0047] In addition, the excessive nucleation caused by the high nucleation sites of perovskite on flexible substrates results in small grain size, rough surface, poor uniformity and many grain boundary defects in the formed perovskite film.

[0048] The perovskite light absorption layer of the perovskite solar cell of the present invention is obtained by spin-coating a mixed solution of an organic ammonium halide salt doped with a hydroxybenzoic acid cross-linking agent on a lead iodide film formed from a lead iodide solution and then heating the mixed solution; the hydroxybenzoic acid cross-linking agent contains at least a benzene ring, a hydroxyl group, and a carboxyl group.

[0049] The hydroxybenzoic acid crosslinker, such as p-hydroxybenzoic acid, can partially self-crosslink under certain conditions. The partially crosslinked hydroxybenzoic acid forms a network structure with the uncrosslinked hydroxybenzoic acid through dynamic hydrogen bonding, acting as a scaffold to anchor the perovskite film, effectively releasing mechanical stress during bending and stretching, reducing the Young's modulus of the perovskite film, and achieving excellent mechanical stability for the perovskite solar cell. Furthermore, the benzene rings in the hydroxybenzoic acid are used to achieve π-π stacking, forming charge extraction and transfer channels, and improving the conductivity of the perovskite light absorption layer formed from materials such as crosslinked elastomers. Furthermore, the hydroxyl groups in the hydroxybenzoic acid participate in an esterification reaction with some of the carboxyl groups; the remaining carboxyl groups in the hydroxybenzoic acid act as a catalyst for the esterification reaction; the hydroxybenzoic acid interacts with the perovskite through coordination and hydrogen bonding, promoting the growth of perovskite crystals and passivating grain boundary defects.

[0050] The present invention provides a perovskite solar cell, comprising a substrate, a carrier transport layer located on the substrate, and a perovskite light absorption layer located on the carrier transport layer, wherein the perovskite light absorption layer is modified with a hydroxybenzoic acid crosslinker; the hydroxybenzoic acid crosslinker contains at least a hydroxyl group, a carboxyl group, and a benzene ring.

[0051] The embodiments of the present invention improve at least the photoelectric conversion efficiency and mechanical stability of the flexible perovskite layer simultaneously through modification with a hydroxybenzoic acid crosslinker. The principle is briefly described as follows: Hydroxybenzoic acid crosslinkers with functional groups such as hydroxyl and carboxyl groups can interact with perovskites through coordination bonds and hydrogen bonds, promoting the growth of perovskite crystals, passivating grain boundary defects, and reducing non-radiative recombination losses; the benzene rings in the hydroxybenzoic acid crosslinkers can form charge extraction and transmission channels through π-π stacking, improving the carrier mobility of the perovskite film and improving the problem of poor conductivity; in addition, the cross-linked material forms a network structure at the perovskite grain boundary, acting as a scaffold to anchor the perovskite film, effectively releasing mechanical stress during bending and stretching, reducing the Young's modulus of the perovskite film, and enabling the perovskite solar cell to obtain excellent mechanical stability; at the same time, the dynamic hydrogen bonds in the crosslinker can be rapidly formed under mild conditions, giving the perovskite film a strong self-healing ability.

[0052] In some embodiments, the Young's modulus of the perovskite light absorbing layer is in the range of 24 GPa to 26 GPa. In some embodiments, the electrical conductivity of the perovskite light absorbing layer is in the range of 8×10 -5 S / cm~10×10 -5 Compared with the solution before the improvement, the invention has a significant effect at least in terms of Young's modulus and conductivity.

[0053] The perovskite solar cell described in the embodiments of the present invention, in some embodiments, includes, in addition to a substrate, a first carrier transport layer on the substrate, and a perovskite light absorption layer, a second carrier transport layer, and further includes a first electrode and a second electrode; the first electrode is deposited on the substrate below the first carrier transport layer, the second carrier transport layer is located on the perovskite light absorption layer, and the second electrode is located on the second carrier transport layer.

[0054] In some embodiments, one of the first electrode and the second electrode is an anode, and the other is a cathode. One of the first carrier transport layer and the second carrier transport layer is an electron transport layer, and the other is a hole transport layer.

[0055] One embodiment is shown in Figure 1 As shown, the solar cell includes: a substrate 10, a transparent conductive electrode 11 on the substrate, and the substrate on which the transparent conductive electrode is deposited is called a transparent conductive substrate 10 (11). It also includes an electron transport layer 12 (first carrier transport layer), a perovskite layer 13 (perovskite light absorption layer), a hole transport layer 14 (second carrier transport layer) and a silver electrode 15 (cathode) stacked in sequence on the transparent conductive substrate 10 (11).

[0056] In some embodiments, a method for preparing a perovskite solar cell includes the steps of preparing a perovskite light absorbing layer, specifically comprising:

[0057] S1: Step of preparing a lead iodide thin film: spin-coating a dissolved lead iodide precursor solution on an ITO conductive substrate deposited with an electron transport layer, and performing a heat treatment to prepare a lead iodide thin film;

[0058] In some embodiments, a cathode and an electron transport layer are first fabricated on a flexible or rigid substrate, and the dissolved lead iodide thin film is then spin-coated on the electron transport layer. Spin-coating the lead iodide thin film on the electron transport layer not only makes the lead iodide thin film more uniform and flat, but also regulates perovskite crystal growth, improving battery stability.

[0059] S2: The step of preparing a perovskite film, i.e., a perovskite light absorption layer: spin-coating an organic ammonium halide salt solution containing a hydroxybenzoic acid cross-linking agent on the lead iodide film, and heating the solution to obtain a perovskite film on a carrier transport layer (e.g., an electron transport layer); wherein the hydroxybenzoic acid cross-linking agent contains at least a hydroxyl group, a carboxyl group, and a benzene ring.

[0060] The heating process produces a perovskite film because the heating treatment not only promotes the chemical reaction between lead iodide and the organic halide ammonium salt solution to form perovskite crystals, but also partially self-crosslinks the hydroxybenzoic acid during this process. This self-crosslinking reaction is a type of esterification reaction. The hydroxyl groups in the hydroxybenzoic acid participate in the esterification reaction with some of the carboxyl groups, and the remaining carboxyl groups serve as catalysts for the esterification reaction. The partially crosslinked hydroxybenzoic acid and the uncrosslinked hydroxybenzoic acid form a network structure through dynamic hydrogen bonds, which acts as a scaffold to anchor the perovskite film and reduce the Young's modulus of the perovskite film. At the same time, the benzene rings in the hydroxybenzoic acid are used to achieve π-π stacking to form charge extraction and transfer channels, thereby improving the conductivity of the perovskite crystals formed from materials such as crosslinked elastomers. In addition, the hydroxybenzoic acid crosslinker interacts with the perovskite through coordination bonds and hydrogen bonds, promoting the growth of perovskite crystals and passivating grain boundary defects.

[0061] In step S1, in some embodiments, lead iodide can be dissolved in a mixed solvent of N,N-dimethylformamide (DMF) and dimethyl sulfoxide (DMSO), and then subjected to spin coating and heat treatment to obtain the lead iodide thin film.

[0062] More specifically, in some embodiments, the volume ratio of DMF and DMSO in the mixed solvent of N,N-dimethylformamide DMF and dimethyl sulfoxide DMSO is 19:1; 1.3 to 1.5 mmol of lead iodide PbI2 is dissolved in 1 mL of a mixed solvent of N,N-dimethylformamide DMF and dimethyl sulfoxide DMSO, followed by spin coating at a spin coating rate of 1700 to 1800 r / min and a spin coating time of 25 to 35 s, such as 30 s, and heat treatment is performed at a temperature range of 70 to 100°C for 1 to 2 min to obtain a PbI2 thin film.

[0063] In step S2, in some embodiments, MA containing hydroxybenzoic acid is 0.3 FA 0.7 Br 0.1 I 0.7 Cl 0.2 An organic ammonium halide salt solution is spin-coated on a PbI2 film and heat-treated to obtain a perovskite film. Specifically, in some embodiments, the spin-coating rate is 1500-1700 r / min, the spin-coating time is 20-60 s; annealing is performed on a heating table for 10-60 min, and the annealing temperature is 80-120°C. The organic ammonium halide salt solution is a mixture of formamidinium iodide FAI, methylammonium bromide MABr, and methylammonium chloride MACl in a mass ratio of 10:1:1, and then dissolved in 2 mL of isopropanol solution to form a MACl solution with a concentration of 72 mg / mL. 0.3 FA 0.7 Br 0.1 I 0.7 Cl 0.2 Solution; the MA containing hydroxybenzoic acid 0.3 FA 0.7 Br 0.1 I 0.7 Cl 0.2 The organic ammonium halide salt solution is prepared by adding an isopropyl alcohol solution of hydroxybenzoic acid with a volume of 1 mL and a concentration of 1 to 2 mmol / 1 mL to the above-mentioned organic ammonium halide salt solution.

[0064] In some embodiments, the thickness of the prepared perovskite light absorbing layer is 450-550 nm, for example, 500 nm.

[0065] The substrate is a substrate that plays a supporting role, for example, a rigid glass substrate, or a polyethylene terephthalate (PET) flexible substrate, or a polyethylene naphthalate (PEN) flexible substrate, or a polyimide (PI) flexible substrate.

[0066] For example, the electron transport layer may be, but is not limited to, a SnO2 thin film.

[0067] The following specifically illustrates the technical problems solved and the technical effects achieved by the present application by comparing the preparation methods and performance test data of the improved invention with those of the scheme before the improvement.

[0068] Example 1: Perovskite solar cell modified with p-hydroxybenzoic acid crosslinker according to the present invention

[0069] A specific process for preparing a p-hydroxybenzoate perovskite solar cell includes:

[0070] S1. Cleaning a glass substrate or a flexible substrate on which a cathode (eg, ITO) is deposited. The substrate on which the cathode is deposited is called a conductive substrate.

[0071] Specifically, the method comprises: ultrasonically cleaning the conductive substrate with deionized water, acetone and alcohol for 10 to 15 minutes respectively, and then drying the substrate with pure nitrogen; after cooling to room temperature, treating the conductive substrate with ozone for 10 to 15 minutes.

[0072] S2. Spin-coating an electron transport layer SnO2 on the conductive substrate.

[0073] Specifically, the method includes spin coating a SnO2 precursor solution on a pretreated ITO conductive glass substrate (conductive substrate), and then heat treating the substrate at 150°C for 30 minutes to form an electron transport layer (SnO2 film layer) on the conductive glass substrate.

[0074] S3. Preparation of MA 0.3 FA 0.7 PbBr 0.1 I 2.7 Cl 0.2 The perovskite film specifically includes the following steps:

[0075] S31. For example, 1.3 mmol of lead iodide (PbI2) is dissolved in 1 mL of a mixed solvent of N,N-dimethylformamide (DMF) and dimethyl sulfoxide (DMSO), wherein the volume ratio of DMF to DMSO in the mixed solvent of N,N-dimethylformamide (DMF) and dimethyl sulfoxide (DMSO) is 19:1, to prepare a PbI2 solution.

[0076] S32. The PbI2 solution was then spin-coated at a rate of 1800 r / min for 30 s, and heat-treated at 70° C. for 1 min to obtain a PbI2 thin film.

[0077] S33, then dissolve 2 mmol of p-hydroxybenzoic acid in 1 mL of isopropanol; formammonium iodide FAI, methylammonium bromide MABr, and methylammonium chloride MACl in a mass ratio of 10:1:1, and then dissolve in 2 mL of isopropanol solution to form a MA solution with a concentration of 72 mg / mL. 0.3 FA0.7 Br 0.1 I 0.7 Cl 0.2 Organic ammonium halide mixed solution; then the above two solutions are mixed.

[0078] S34, then MA containing parahydroxybenzoic acid 0.3 FA 0.7 Br 0.1 I 0.7 Cl 0.2 The organic ammonium halide mixed solution was spin-coated on the PbI2 film at a spin-coating rate of 1700 r / min for 30 s, and then heat-treated at 100°C for 25 min to obtain a perovskite light absorption layer.

[0079] S4, spin coating a hole transport layer Spiro-OMeTAD on the conductive substrate.

[0080] Specifically, 540 mg of lithium bis(trifluoromethanesulfonyl)imide was dissolved in 1 mL of acetonitrile solution and shaken thoroughly to obtain Li-TFSI acetonitrile solution; 720 mg of 2,2,7,7′-tetrakis[N,N′-bis(4-methoxyphenyl)amino]-9,9′-spirobifluorene solution (Spiro-OMeTAD) was then dissolved in 1 mL of chlorobenzene, and 18 μL of Li-TFSI acetonitrile solution and 29 μL of 4-tert-butylpyridine is fully shaken to obtain a 2,2,7,7′-tetrakis[N,N′-bis(4-methoxyphenyl)amino]-9,9′-spirodifluorene chlorobenzene solution containing Li-TFSI and 4-tert-butylpyridine dopant; finally, the mixed solution is spin-coated on the perovskite light absorption layer by a solution spin coating method at a spin coating rate of 4000 rpm and a spin coating time of 25 to 35 s, for example, 30 s, to obtain a hole transport layer Spiro-OMeTAD.

[0081] Spin coating the hole transport layer on the conductive substrate is an optional embodiment. In some products or embodiments, the hole transport layer may not be formed.

[0082] S5. Vapor-depositing a metal Ag electrode (anode) on the hole transport layer to obtain a perovskite solar cell modified with a hydroxybenzoic acid crosslinker.

[0083] Comparative Example 1:

[0084] The difference from Example 1 lies in: Steps S33-S34.

[0085] In step S33 of the control example, formammonium iodide FAI, methylammonium bromide MABr, and methylammonium chloride MACl were mixed in a mass ratio of 10:1:1 and then dissolved in 2 mL of isopropanol solution to form MACl with a concentration of 72 mg / mL.0.3 FA 0.7 Br 0.1 I 0.7 Cl 0.2 Organic ammonium halide mixed solution.

[0086] In the control example, step S34, MA 0.3 FA 0.7 Br 0.1 I 0.7 Cl 0.2 The organic ammonium halide mixed solution was spin-coated on the PbI2 film at a spin-coating rate of 1700 r / min for 30 s, and then heat-treated at 100°C for 25 min to obtain a perovskite light absorption layer modified with a hydroxybenzoic acid-free crosslinker.

[0087] The test results are as follows:

[0088] Attachment Figure 1 This is a diagram of the structure of a perovskite solar cell produced in an embodiment of the present invention. From bottom to top, it includes a transparent conductive substrate, an electron transport layer, a perovskite layer, a hole transport layer, and a silver electrode.

[0089] Attachment Figure 2 This is a scanning electron microscope morphology image of the perovskite light absorption layer prepared in an embodiment of the present invention. Figure 2 (a) is the surface morphology of the perovskite light absorption layer of the control group tested based on scanning electron microscopy; Figure 2 (b) is a surface morphology of the perovskite light absorption layer modified with a hydroxybenzoic acid crosslinker tested based on a scanning electron microscope in an embodiment of the present invention; after testing, the average size of the perovskite grains modified with the crosslinker increased from 584 nm of the control film to 937 nm, and the grains at the grain boundaries were relatively smooth and dense. This is because the p-hydroxybenzoic acid crosslinker promoted crystal growth and reduced grain boundary defects, so the perovskite light absorption layer formed was uniform, dense, and had a high degree of crystallinity.

[0090] Attachment Figure 3 This is an atomic force microscope image of the perovskite light absorption layer prepared in this example. Figure 3 (a) is the morphology of the perovskite light absorption layer of the control group tested based on atomic force microscopy; Figure 3 (b) is a morphology of the perovskite light absorption layer modified with a hydroxybenzoic acid crosslinker tested by atomic force microscopy in an embodiment of the present invention; the surface roughness of the perovskite film with a crosslinker is improved from 24.2 nm of the control film to within 12 nm, for example Figure 3 (b) shows that the roughness is improved to 11.5 nm. This smoother surface is beneficial for enhancing the contact with the carrier transport layer and improving the extraction of carriers.

[0091] Attachment Figure 4 This is the conductivity diagram of the perovskite light absorption layer prepared in this embodiment. Figure 4 (a) is the conductivity diagram of the perovskite light absorption layer of the control group; Figure 4 (b) is the conductivity spectrum of the perovskite light absorbing layer modified with a hydroxybenzoic acid crosslinker. After testing, the conductivity of the perovskite light absorbing layer with a crosslinker in the embodiment of the present invention is in the range of 8×10 -5 S / cm~10×10 -5 S / cm, preferably 9×10 -5 S / cm~9.6×10 -5 S / cm, for example, 9.3×10 -5 S / cm.

[0092] The above example was obtained from the control film of 7.1×10 -5 S / cm is increased to at least 9.3×10 -5 S / cm.

[0093] Attachment Figure 5 The current density-voltage curve of the rigid perovskite solar cell prepared in this embodiment. Figure 5 (a) is the current density-voltage curve of the control group rigid perovskite solar cell measured under AM1.5G sunlight; Figure 5 (b) is the current density-voltage curve of the rigid perovskite solar cell modified by the crosslinker; compared with the perovskite solar cell in the control group, the short-circuit current density of the perovskite solar cell modified by the crosslinker in the embodiment of the present invention is increased from 24.30 mA / cm 2 Increased to 25.77mA / cm 2 , the open circuit voltage increased from 1.169V to 1.194V, and the photoelectric conversion efficiency increased from 22.32% to 24.76%.

[0094] Example 2: Flexible perovskite solar cells modified with p-hydroxybenzoic acid crosslinker.

[0095] In Example 1, the substrate used is a rigid substrate. In this embodiment, a flexible substrate is used instead. The conductive flexible substrate with ITO (cathode) deposited thereon is fixed on the white glass using UV glue.

[0096] In the above step S2, the heat treatment temperature of the spin-coated SnO2 film (electron transport layer) is changed to 100°C;

[0097] In the above step S3, the spin coating rate of the PbI2 solution was changed to 1700 r / min; the MA containing p-hydroxybenzoic acid 0.3 FA 0.7 Br 0.1 I 0.7 Cl0.2 The spin coating rate of the organic ammonium halide mixed solution was changed to 1500 r / min, and the heat treatment temperature was changed to 100°C.

[0098] Comparative Example 2:

[0099] The difference from Example 2 is that steps S33-S34 are changed to:

[0100] S33, formammonium iodide FAI, methylammonium bromide MABr, and methylammonium chloride MACl were mixed in a mass ratio of 10:1:1, and then dissolved in 2 mL of isopropanol solution to form MACl with a concentration of 72 mg / mL. 0.3 FA 0.7 Br 0.1 I 0.7 Cl 0.2 Organic ammonium halide mixed solution.

[0101] S34, then MA 0.3 FA 0.7 Br 0.1 I 0.7 Cl 0.2 The organic ammonium halide mixed solution was spin-coated on the PbI2 film at a spin-coating rate of 1700 r / min for 30 s, and then heat-treated at 100°C for 25 min to obtain an unmodified perovskite light absorption layer.

[0102] The test results are as follows:

[0103] Attachment Figure 6 This is the nanoindentation test graph of the perovskite light absorption layer prepared in this embodiment. Figure 3 (a) is the nanoindentation test spectrum of the perovskite light absorption layer of the control group; Figure 3 (b) shows the nanoindentation test of the perovskite light-absorbing layer modified with a hydroxybenzene crosslinker. It can be seen that the Young's modulus of the perovskite light-absorbing layer modified with a hydroxybenzene crosslinker decreases from 40.19 GPa to 25.05 GPa. This reduction in Young's modulus improves the flexibility of the perovskite film.

[0104] Attachment Figure 7 The current density and voltage curves of the flexible perovskite solar cell prepared in this embodiment are shown. Figure 7 (a) shows the current density and voltage curves of the flexible perovskite solar cell measured under AM1.5G sunlight; Figure 7 (b) Current density and voltage curve of flexible perovskite solar cells modified by crosslinkers. Compared with the control group perovskite solar cells, the short-circuit current density of the perovskite solar cells modified by crosslinkers increased from 22.49 mA / cm 2 Increased to 23.63mA / cm2 , the open circuit voltage increased from 1.166V to 1.199V, and the photoelectric conversion efficiency increased from 20.69% to 22.73%.

[0105] Attachment Figure 8 A normalized statistical graph of the efficiency of the flexible perovskite solar cell prepared in this embodiment after being bent 10,000 times at a bending radius of 5 mm. Figure 8 (a) is the normalized statistical graph of the efficiency of the flexible perovskite solar cell in the control group after being bent 10,000 times at a bending radius of 5 mm. Figure 8 Figure (b) shows the normalized efficiency of a flexible perovskite solar cell modified with a p-hydroxybenzoic acid crosslinker, according to an embodiment of the present invention, after 10,000 bends at a 5mm bend radius. The crosslinker-modified flexible device maintained 91% of its original efficiency after 10,000 bend cycles, while the control flexible perovskite solar cell had zero efficiency after 4,000 bend cycles.

[0106] Attachment Figure 9 This is a normalized statistical graph of the efficiency of the flexible perovskite solar cell after self-healing treatment obtained in this embodiment. Figure 9 (a) is the normalized statistical graph of the efficiency of the control group flexible perovskite solar cell after self-healing treatment; Figure 9 (b) Normalized statistical graph of the efficiency of flexible perovskite solar cells modified with crosslinkers after self-healing treatment; the crosslinker-treated flexible device can recover to 89% of the original efficiency after self-healing treatment, while the flexible perovskite solar cell in the control group can only recover to 45% of the original efficiency.

[0107] The light-absorbing layer of a perovskite solar cell provided by the present invention is obtained by spin-coating a mixed solution of an organic ammonium halide salt doped with a hydroxybenzoic acid crosslinker onto a lead iodide film formed from a lead iodide solution, followed by heat treatment. This method can at least reduce the Young's modulus of the perovskite film while maintaining high electrical conductivity without causing device insulation and loss of photoelectric performance.

[0108] Finally, it should be noted that the above is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or make equivalent substitutions for some of the technical features therein. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. A method for preparing a perovskite solar cell, comprising the steps of preparing a perovskite light absorbing layer on a substrate, characterized in that: The perovskite light absorbing layer is modified with a hydroxybenzoic acid cross-linking agent; The steps of preparing the perovskite light absorbing layer include: The lead iodide thin film is prepared by spin coating the dissolved lead iodide precursor solution on a substrate with a carrier transport layer deposited on the surface, and then heating the substrate. Spin-coating an organic ammonium halide salt solution containing a hydroxybenzoic acid cross-linking agent on the lead iodide film, and heating the solution to obtain a perovskite light absorption layer on the carrier transport layer; Wherein, the hydroxybenzoic acid cross-linking agent contains at least a hydroxyl group, a carboxyl group and a benzene ring.

2. The preparation method according to claim 1, characterized in that The hydroxybenzoic acid crosslinking agent is one of p-hydroxybenzoic acid, o-hydroxybenzoic acid, m-hydroxybenzoic acid, 2-hydroxyterephthalic acid, and 2-hydroxy-1,3,5-benzenetricarboxylic acid.

3. The preparation method according to claim 1 or 2, characterized in that The lead iodide thin film is prepared by spin coating the dissolved lead iodide precursor solution on a substrate having a carrier transport layer deposited on the surface thereof, and then heating the substrate. Specifically, the process comprises: Dissolving lead iodide in a mixed solvent of N,N-dimethylformamide (DMF) and dimethyl sulfoxide (DMSO), and then performing a spin coating process and an annealing process to prepare the lead iodide film; An organic ammonium halide salt solution containing a hydroxybenzoic acid crosslinking agent is spin-coated on the lead iodide film, and subjected to heat treatment to obtain a perovskite light absorption layer located on the carrier transport layer, specifically comprising: MA containing the hydroxybenzoic acid cross-linking agent x FA 1-x Br y I z Cl 1-y-z An organic ammonium halide salt solution is spin-coated on the lead iodide film and subjected to heat treatment to obtain a perovskite light absorption layer in contact with the carrier transport layer; wherein x is a number less than 1, and y and z are numbers less than 1.

4. The preparation method according to claim 3, characterized in that The spin coating and annealing conditions for preparing the lead iodide film include: a spin coating rate ranging from 1700 to 1800 r / min, a spin coating time ranging from 25 to 35 s; an annealing temperature ranging from 70 to 100° C. on a heating table, and an annealing time ranging from 1 to 2 minutes; The spin coating and annealing conditions for preparing the perovskite light absorbing layer include: a spin coating rate ranging from 1500 to 1700 r / min, a spin coating time ranging from 20 to 60 s; an annealing time ranging from 10 to 60 min on a heating stage, and an annealing temperature ranging from 80 to 120° C.

5. The preparation method according to claim 4, characterized in that The volume ratio of the mixed solvent of N, N-dimethylformamide DMF and dimethyl sulfoxide DMSO is 19:1; MA containing the hydroxybenzoic acid cross-linking agent x FA 1-x Br y I z Cl 1-y-z The concentration of the hydroxybenzoic acid cross-linking agent in the organic ammonium halide solution is 1 to 2 mmol / mL; The organic halide ammonium salt mixed solution is a mixture of formammonium iodide FAI, methylammonium bromide MABr, and methylammonium chloride MACl, which is then dissolved in an isopropanol solution to form MACl. x FA 1-x Br y I z Cl 1-y-z solution.

6. A perovskite solar cell, characterized in that: The invention comprises a substrate, a first carrier transport layer located on the substrate, and a perovskite light absorption layer located on the first carrier transport layer and in contact with the first carrier transport layer, wherein the perovskite light absorption layer is modified with a hydroxybenzoic acid crosslinker; the hydroxybenzoic acid crosslinker contains at least a hydroxyl group, a carboxyl group and a benzene ring.

7. The perovskite solar cell according to claim 6, characterized in that The Young's modulus of the perovskite light absorbing layer is in the range of 24 GPa-26 GPa.

8. The perovskite solar cell according to claim 7, characterized in that The conductivity of the perovskite light absorbing layer is in the range of 8×10 -5 S / cm~10×10 -5 S / cm.

9. The perovskite solar cell according to claim 6, characterized in that It also includes a first electrode located on the substrate; the first electrode is located between the substrate and the first carrier transport layer; The invention also includes a second carrier transport layer and a second electrode which are sequentially located on the perovskite light absorbing layer.

10. The perovskite solar cell according to claim 9, characterized in that The first carrier transport layer is an electron transport layer, the second carrier transport layer is a hole transport layer, the first electrode is a cathode, and the second electrode is an anode; or The first carrier transport layer is a hole transport layer, the second carrier transport layer is an electron transport layer, the first electrode is an anode, and the second electrode is a cathode.

11. A perovskite solar cell, characterized in that: It is prepared by the preparation method according to any one of claims 1 to 5.

Citation Information

Patent Citations

  • Perovskite film layer capable of effectively improving efficiency of luminescent device, device and preparation method

    CN109980095A

  • Preparation method of perovskite device

    CN116367672A

  • Method for improving quality of perovskite thin film, perovskite thin film and solar cell

    CN119233734A

  • Perovskite precursor solution, perovskite precursor film and perovskite crystallization regulation and control method

    CN119836207A

  • Rotor for compressor and method for manufacturing the rotor for compressor

    KR1020240002029A